Results of ISI Implementation in Uzbekistan (in The Example of Uzbek Automotive Industry): Achievements and Negative Outcomes - Ziyodulla Nurov; Gulnora Nurova (Garuda Prestasi Nusantara Consulting, 2021)
Since independence, policymakers have tried to set trade restrictions. As a result, the Uzbek economy has gained some positive outcomes and experienced difficulties relating to this policy as well. In this regard, the article presents how ISI (Import-Substituting Industrialization) policy caused the appearance of at least one multinational enterprise for the production of cars and components in the Uzbek automobile industry, as well as a comfortable entrepreneur environment for local firms and other privileges of ISI policy to some extent. Moreover, the article shows negatives of ISI, as well. As advocated in many studies, ISI policy causes some negative results, such as restrictions on market access, weak competitive environment, consumer welfare problems, and so on. Key words. Import-Substituting Industrialization, Policy implementation, Negative outcomes, Positive outcomes, Uzbek automotive industry.